2014
DOI: 10.1186/1746-160x-10-48
|View full text |Cite
|
Sign up to set email alerts
|

Headache prevalence and its characterization amongst hospital workers in Enugu, South East Nigeria

Abstract: BackgroundHeadaches are probably the commonest neurological complaint worldwide. Amongst workers it contributes significantly to loss of productive time and work efficiency. It is an important cause of disability and reduced quality of life. The prevalence and pattern amongst health workers in Africa has not been extensively studied.ObjectiveThis epidemiological sampling-based preliminary study examined the frequency and pattern of headache in a population of health workers of a tertiary hospital in Enugu, Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
2
9
3
Order By: Relevance
“…In the student population of this study the life time prevalence of headache was 81.11 % which is close to a community based report from Addis Ababa (83.1 %) [ 27 ] and Singapore (82.7 %) [ 28 ]. But the prevalence of headache in this study is higher than a report from undergraduate student headache prevalence of Southern Brazil 74.5 % [ 29 ] and lower than other reports from Brazil [ 30 , 31 ] and Nigeria 88 % [ 32 ]. The last 1 year prevalence of headache in our study population was 67.22 % and this is still closer to the report from Addis Ababa (67.5 %) [ 27 ] and lower than the report from Brazil which was 91 % and the discrepancy might be due to methodological, study population or real difference [ 30 ].…”
Section: Discussioncontrasting
confidence: 92%
“…In the student population of this study the life time prevalence of headache was 81.11 % which is close to a community based report from Addis Ababa (83.1 %) [ 27 ] and Singapore (82.7 %) [ 28 ]. But the prevalence of headache in this study is higher than a report from undergraduate student headache prevalence of Southern Brazil 74.5 % [ 29 ] and lower than other reports from Brazil [ 30 , 31 ] and Nigeria 88 % [ 32 ]. The last 1 year prevalence of headache in our study population was 67.22 % and this is still closer to the report from Addis Ababa (67.5 %) [ 27 ] and lower than the report from Brazil which was 91 % and the discrepancy might be due to methodological, study population or real difference [ 30 ].…”
Section: Discussioncontrasting
confidence: 92%
“…As reported in previous almost all studies13-15 female predominance is seen in our study (female/male ratio 195/92=2, 1). The influence of oestrogens and progesterone on headaches after menarche and the greater propensity for females to seek medical attention for headaches are the most evocated reasons to explain this higher female prevalence 16…”
Section: Discussionsupporting
confidence: 91%
“…We found that the 1-year prevalence of primary headache disorders among medical staff in Sanya, South China, was 50% (migraine: 25.9%; TTH: 24.1%), which was significantly higher than the 23.8% (migraine: 9.3%; TTH: 10.8%) obtained in a populationbased study in mainland China [3]. The prevalence rate of hospital workers in previous literature was high, as Sokolovic reported a 3-month prevalence of 61% [24], and Onwuekwe showed that the half-year prevalence was more than 70% [25]. There are two possible reasons for the difference.…”
Section: Discussionmentioning
confidence: 60%